Metal ions contamination in ground water of Kathmandu and removal of iron using adsorbent prepared from natural resources - Jha, Vinay Kumar; Khatri, Ram Bahadur (Scientific World, 2011)
Some metal ions contaminations of underground water have been assessed in Kathmandu. A total of ten water samples, randomly collected from deep tube wells and shallow wells, were analyzed for metal ions by AAS. The comparison of the data of physico-chemical properties of contaminated ground water showed that pH, sodium, potassium, zinc, lead and cadmium lie within the WHO guideline value for drinking water whereas, the concentration of iron was found to be higher in almost all underground water samples. Adsorbents for Fe ion removal were prepared from various resources such as crab’s shell powder, silica stone powder, hen’s eggshell powder and limestone powder. The adsorbent prepared from hen’s eggshell was found appropriate and cost effective resource to remove Fe ions from aqueous solution and the maximum Fe ion adsorption capacity for such an adsorbent was 0.24 mg/g. The Langmuir type adsorption isotherm was found to fit in the experimental data than the Freundlich isotherm. Keywords: Underground water of Kathmandu valley; Fe adsorption; Eggshell powder; Langmuir adsorption isotherm. DOI: http://dx.doi.org/10.3126/sw.v9i9.5517 SW 2011; 9(9): 44-49